Copper alloy current collector of aqueous zinc ion battery, production method and application
By using the copper alloy alloy alloy fluid prepared by vacuum melting and process processing in the water -based zinc cells, the problem of branches crystal is solved, the battery life is improved and the production cost is reduced.
Patent Information
- Application Number
- CN202411032834.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-30
AI Technical Summary
The dendrite problem in zinc negative electrode is a major reason that restricts the cycle life of zinc batteries. The existing current collector modification methods are costly and are not suitable for large-scale production.
A copper alloy current collector for an aqueous zinc-ion battery is used, which is prepared through steps such as vacuum smelting, cutting, rolling and annealing. The process has low cost, is easy to implement, and inhibits dendrite growth.
Effectively inhibits dendrite growth, improves battery life, reduces production costs, and is suitable for mass production.
Smart Images

Figure CN119346852A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of negative electrodes of aqueous zinc ion batteries, and in particular to a copper alloy current collector, a production method and an application of an aqueous zinc ion battery. Background Art
[0002] Lithium-ion batteries occupy half of the current secondary battery market due to their advantages such as high energy density. However, safety accidents involving lithium-ion batteries occur frequently, and the price of metallic lithium is relatively high. Therefore, people are constantly exploring solutions to replace lithium-ion batteries. Currently, aqueous zinc-ion batteries have attracted much attention due to their advantages of low cost and high safety.
[0003] However, the dendrite problem in the zinc negative electrode is a major reason that restricts the cycle life of zinc batteries. One of the solutions is current collector modification, which can be divided into three-dimensional current collector modification, surface coating modification, and alloy current collector modification. Among them, the first two are relatively expensive and are not suitable for large-scale production. The current alloy production process is relatively mature. Copper is often used as the negative electrode current collector, but the deposition of zinc on pure copper will inevitably be accompanied by dendrite growth, so it is necessary to improve it. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a copper alloy current collector for an aqueous zinc ion battery, a production method and an application thereof, which has low process cost, is easy to implement, inhibits dendrite growth, is applied to the negative electrode of an aqueous zinc ion battery and improves the battery life.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is: a method for producing a copper alloy current collector for an aqueous zinc ion battery, comprising the following steps:
[0006] Step S1, weighing various metal powders according to weight percentage, including 0.1-3wt% of tin and the balance of copper;
[0007] Step S2, moving each metal powder into a graphite crucible, placing the graphite crucible in a vacuum device, and maintaining the vacuum degree of the vacuum chamber at 20-1 Pa;
[0008] Step S3, heating and smelting, the smelting temperature is controlled at 900-1500° C., and heating is stopped after all the metal powders are melted, and pouring is performed in a vacuum cavity and cooled to room temperature to obtain a copper alloy ingot;
[0009] Step S4, cutting the copper alloy ingot into sheets with a thickness of 0.5 to 1 cm to obtain copper alloy sheets,
[0010] Step S5, performing a first rolling treatment on the copper alloy sheet, and reducing the thickness of the copper alloy sheet to 200-400 μm by the first rolling treatment; and then performing a first annealing treatment on the copper alloy sheet.
[0011] The first annealing treatment includes a heating stage, a heat preservation stage and a cooling stage, in which atmosphere protection is performed in the heating stage, the heat preservation stage and the cooling stage. In the heating stage, the heating rate is controlled at 5 to 10°C / min, in the heat preservation stage, the annealing temperature is controlled at 400 to 500°C, and the annealing heat preservation time is controlled at 1 to 4 hours. In the cooling stage, the copper alloy sheet is naturally cooled to room temperature in the atmosphere protection;
[0012] Step S6, performing a second rolling treatment on the copper alloy sheet that has undergone the first annealing treatment, reducing the thickness of the copper alloy sheet to 70-150 μm by the second rolling treatment, and then performing a second annealing treatment on the copper alloy sheet.
[0013] The second annealing treatment includes a heating stage, a heat preservation stage and a cooling stage. Atmosphere protection is performed in the heating stage, the heat preservation stage and the cooling stage. In the heating stage, the heating rate is controlled at 5-10°C / min. In the heat preservation stage, the annealing temperature is controlled at 400-500°C and the annealing holding time is controlled at 1-4 hours. In the cooling stage, the copper alloy sheet is naturally cooled to room temperature in the atmosphere protection.
[0014] A copper alloy current collector for an aqueous zinc ion battery is prepared.
[0015] Furthermore, during the first annealing treatment, the heating rate is controlled at 8-10°C / min in the heating stage, the annealing temperature is controlled at 400-450°C, and the annealing holding time is controlled at 1-2 hours in the holding stage; the thickness of the copper alloy sheet is thinned to 70-100 μm through the second rolling treatment, and during the second annealing treatment, the heating rate is controlled at 5-6°C / min in the heating stage, the annealing temperature is controlled at 460-500°C, and the annealing holding time is controlled at 0.5-1 hour in the holding stage.
[0016] Furthermore, in the step S3, the smelting temperature is controlled at 900-1000°C, and the smelting time is controlled at 0.3-0.5 hours; in the step S5, during the first annealing process and the second annealing process, the atmosphere used for the atmosphere protection is a mixed atmosphere of hydrogen and argon.
[0017] A copper alloy current collector for an aqueous zinc ion battery is prepared according to a production method for a copper alloy current collector for an aqueous zinc ion battery. The copper alloy current collector comprises 0.1 to 3 wt % of tin and the remainder of copper, as well as inevitable impurity elements, by weight percentage. The tin element is completely dissolved in a copper matrix, and there is no enrichment of tin or copper elements at or within the grain boundaries. The grains are distributed in an equiaxed crystal shape, the grain radius is 2 to 5 microns, and the size difference of the grains in each direction is reduced to 0.1 to 0.5 microns.
[0018] Furthermore, the copper alloy current collector also includes 0.1-3wt% indium or 0.1-3wt% silver by weight, wherein the indium element or the silver element is completely dissolved in the copper matrix, and there is no enrichment of tin element, copper element, indium element or silver element at and within the grain boundaries. The grains are distributed in an equiaxed crystal shape, the grain radius is 2-3 microns, and the size difference of the grains in each direction is reduced to 0.1-0.3 microns.
[0019] Furthermore, the copper alloy current collector also includes 0.1-1wt% indium and 0.1-1wt% silver by weight, wherein tin, indium and silver are completely dissolved in the copper matrix, and there is no enrichment of tin, copper, indium or silver at and within the grain boundaries. The grains are distributed in an equiaxed crystal shape, the grain radius is 2-3 microns, and the size difference of the grains in each direction is reduced to 0.1-0.3 microns.
[0020] The invention discloses an application of a copper alloy current collector in an aqueous zinc ion battery. The negative electrode of the aqueous zinc ion battery comprises a whole body obtained by pre-depositing a zinc sheet on the copper alloy current collector.
[0021] Compared with the prior art, the present invention has the following advantages: the present invention simplifies the preparation process of the copper alloy current collector, is easy to implement and easy to control the crystals of the copper alloy current collector, and can produce the copper alloy current collector in large quantities at one time with the help of vacuum melting technology, thereby reducing production costs and having broad prospects for industrial production.
[0022] The preparation method of the present invention thins the alloy by cutting and rolling technology, has no strict size requirements on the alloy ingot raw material, is applicable to most alloy materials, and introduces annealing during rolling to eliminate the stress influence caused by strain.
[0023] The copper alloy current collector prepared by the present invention is applied to the negative electrode of an aqueous zinc ion battery to improve the lattice matching degree between zinc and the substrate during deposition, inhibit dendrite growth, and assemble the copper alloy current collector and zinc foil into an asymmetric battery to maintain a high reversibility of zinc deposition / ejection, thereby greatly improving the coulombic efficiency of the asymmetric battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1is a flow chart for preparing the alloy current collector in the present invention;
[0025] Figure 2 The SEM image and EDS Mapping image of the Cu-0.3Sn alloy current collector in Example 1 of the present invention;
[0026] Figure 3 TEM image of the Cu-0.3Sn alloy current collector in Example 1 of the present invention;
[0027] Figure 4 This is a half-cell cycle diagram of the Cu-0.3Sn alloy current collector in Example 2 of the present invention;
[0028] Figure 5 This is a SEM image of the Cu-2Sn alloy current collector in Example 3 of the present invention;
[0029] Figure 6 This is a half-cell cycle diagram of the Cu-2Sn alloy current collector in Example 3 of the present invention;
[0030] Figure 7 This is a half-cell cycle diagram of the Cu-1Sn alloy current collector in Example 4 of the present invention;
[0031] Figure 8 TEM image of the Cu-0.3Ag alloy current collector in Comparative Example 1 of the present invention;
[0032] Fig. 9 TEM image of the Cu-0.3In alloy current collector in Comparative Example 2 of the present invention;
[0033] Fig.10 This is a half-cell cycle diagram of the Cu current collector in Comparative Example 3 of the present invention;
[0034] Fig.11 These are SEM images of the four current collectors of the present invention after cyclic failure. DETAILED DESCRIPTION
[0035] Example 1
[0036] The preparation method of Cu-0.3Sn alloy current collector comprises the following steps: composition design, melting, cutting, first rolling, first annealing, second rolling, second annealing, copper alloy current collector, such as Figure 1 shown.
[0037] Step S1, weigh 997g of copper and 3g of tin respectively;
[0038] Step S2, moving the weighed metal into a graphite crucible, and placing the graphite crucible in a vacuum device with a vacuum degree of 2 Pa;
[0039] Step S3, the smelting temperature is 950° C., after smelting for 0.5 h, the smelting is performed in a vacuum chamber and then cooled to room temperature to obtain a Cu-0.3Sn alloy ingot;
[0040] Step S4, cutting the Cu-0.3Sn alloy ingot into 2 cm thick Cu-0.3Sn alloy sheets;
[0041] Step S5, after the first rolling to 200 μm, a first annealing is performed at 450° C. for 2 hours in a mixed atmosphere of hydrogen and argon, wherein the heating rate is 10° C. / min;
[0042] Step S6, performing a second rolling treatment, rolling the Cu-0.3Sn alloy sheet after the first annealing treatment to a thickness of 100 μm; finally, performing a second annealing treatment in a mixed atmosphere of hydrogen and argon at 460°C for 1 hour, wherein the heating rate is 5°C / min, to obtain a Cu-0.3Sn alloy current collector.
[0043] Step S5 adopts a combination of two rolling and two annealing treatments. The second annealing treatment reduces the heating rate and increases the annealing temperature relative to the third annealing treatment, which not only reduces processing energy consumption, but also reduces the difficulty of thinning, and can better and faster remove the internal stress of the copper alloy current collector.
[0044] The prepared Cu-0.3Sn alloy current collector was subjected to SEM and TEM tests, and its microscopic characteristics are as follows: Figure 2 and Figure 3 As shown, Figure 2 The grain image and EDS Mapping diagram of the Cu-0.3Sn alloy current collector show that the grains are equiaxed, that is, the size difference in each direction is small, the grain radius size is 2 to 3 microns, and there is no single element enrichment at the triple grain boundary and in the grain. Among them, Sn is uniformly dissolved in the Cu matrix; Figure 3 This is the TEM image of the Cu-0.3Sn alloy current collector. The atoms are arranged evenly and neatly without any precipitated phase. According to calculation, the interplanar spacing is 0.185nm. Compared with the interplanar spacing of pure copper, the interplanar spacing of the alloy increases after Sn doping.
[0045] The purpose of the first rolling treatment is to initially reduce the thickness of the alloy. During the rolling process, stress will be generated inside the alloy, causing the alloy to harden and unable to be thinned further. Therefore, the first annealing is performed to eliminate internal stress; the purpose of the second rolling treatment is to make the alloy reach the expected thickness. The actual thickness can be thinned as needed. The purpose of the second annealing is the same as the first annealing, both of which are to eliminate stress and soften the alloy.
[0046] Example 2
[0047] The prepared Cu-0.3Sn current collector was assembled with zinc foil of commercial aqueous zinc ion battery into a half-cell, and the Cu-0.3Sn alloy current collector was tested.
[0048] The positive electrode is selected from one of a manganese-based compound, a vanadium-based compound, HATN or HATN-3CN; the diaphragm is selected from one of a glass fiber diaphragm, a cellulose diaphragm, a polyethylene non-woven diaphragm, and a microporous filter paper; the aqueous electrolyte is composed of a soluble salt and water, and the concentration of the soluble salt is 1 to 5 mol L -1 ;
[0049] The soluble salt includes one of zinc sulfate heptahydrate, zinc trifluoromethanesulfonate and zinc chloride, or the soluble salt is a mixture of at least two of zinc sulfate heptahydrate, zinc trifluoromethanesulfonate and zinc chloride.
[0050] Weigh 5.7512g ZnSO 4 7H 2 O, add 7.48 mL of deionized water to prepare 2 M ZnSO 4 The prepared Cu-0.3Sn current collector was assembled with commercial zinc foil into a half-cell as the electrolyte. -2 , 1mAh cm -2 The coulombic efficiency and cycle stability were tested under the following conditions: Figure 4 As shown, it can maintain a stable cycle for more than 2600 turns.
[0051] Example 3
[0052] The preparation of Cu-2Sn alloy current collector comprises the following steps:
[0053] Step S1, weigh 997g of copper and 20g of tin respectively;
[0054] Step S2, moving the weighed metal into a graphite crucible, and placing the graphite crucible in a vacuum device with a vacuum degree of 5 Pa;
[0055] Step S3, the smelting temperature is 1050° C., after smelting for 2 hours, the smelting is performed in a vacuum chamber and cooled to room temperature to obtain a Cu-2Sn alloy ingot;
[0056] Step S4, cutting the Cu-2Sn alloy ingot into 3 cm thick Cu-2Sn alloy sheets;
[0057] Step S5, after the first rolling to 250 μm, a first annealing treatment is performed in a mixed atmosphere of hydrogen and argon at 400° C. for 1 hour, wherein the heating rate is 5° C. / min;
[0058] Step S6, rolling for the second time, that is, rolling the Cu-2Sn alloy sheet after the first annealing treatment to a thickness of 80 μm; finally, performing a second annealing treatment at 400°C for 1 hour in a mixed atmosphere of hydrogen and argon to obtain a Cu-2Sn alloy current collector. The prepared Cu-2Sn alloy current collector was characterized by SEM, and its organizational characteristics are as follows Figure 5 As shown, the grains are mostly equiaxed and the grain size is relatively uniform.
[0059] The prepared Cu-2Sn current collector was assembled with zinc foil of a commercial aqueous zinc ion battery into a half-cell.
[0060] Weigh 5.7512g ZnSO 4 7H 2 O, add 7.48 mL of deionized water to prepare 2 M ZnSO 4 The prepared Cu-2Sn current collector was assembled with commercial zinc foil as the electrolyte to form a half-cell. -2 , 1mAh cm -2 The coulombic efficiency and cycle stability were tested under the following conditions: Figure 6 As shown, it can maintain a stable cycle for more than 2200 turns.
[0061] Example 4
[0062] The preparation of Cu-1Sn alloy current collector comprises the following steps:
[0063] Step S1, weigh 997g of copper and 10g of tin respectively;
[0064] Step S2, moving the weighed metal into a graphite crucible, and placing the graphite crucible in a vacuum device with a vacuum degree of 3 Pa;
[0065] Step S3, the smelting temperature is 1050° C., after smelting for 1 hour, the smelting is performed in a vacuum chamber and cooled to room temperature to obtain a Cu-1Sn alloy ingot;
[0066] Step S4, cutting the Cu-1Sn alloy ingot into 1 cm thick Cu-1Sn alloy sheets;
[0067] Step S5, after the first rolling to 250 μm, a first annealing is performed at 400° C. for 1 hour in a mixed atmosphere of hydrogen and argon, wherein the heating rate is 5° C. / min;
[0068] Step S6, performing a second rolling, that is, rolling the Cu-1Sn alloy sheet after the first annealing treatment to a thickness of 100 μm; finally, performing a second annealing treatment, the operation is the same as the first annealing treatment, to obtain a Cu-1Sn alloy current collector.
[0069] Weigh 5.7512g ZnSO 4 7H 2 O, add 7.48 mL of deionized water to prepare 2 M ZnSO 4 The prepared Cu-1Sn current collector was used as the electrolyte and assembled with commercial zinc foil into a half-cell. -2 , 1mAh cm -2 The coulombic efficiency and cycle stability were tested under the following conditions: Figure 7 As shown, it can maintain a stable cycle for more than 2400 turns.
[0070] Comparative Examples 1-2
[0071] Cu-0.3Ag alloy current collector and Cu-0.3In alloy current collector were prepared.
[0072] According to the same process and test conditions as in Examples 1 to 2, Cu-0.3Ag alloy current collector and Cu-0.3In alloy current collector were prepared respectively. As shown in Table 1, doping a small amount of alloying elements in copper can adjust the interplanar spacing of the matrix, thereby reducing the mismatch with Zn, which is beneficial to the deposition of Zn on the current collector and improving battery performance. The three copper alloys proposed in this patent can achieve the above effects, among which Cu-0.3Sn current collector has the best effect. The TEM images of Cu-0.3Ag and Cu-0.3In alloy current collectors are shown in Figure 1. Figure 8 and Fig. 9 As shown, Figure 8 This is the TEM image of the Cu-0.3Ag alloy current collector. According to calculations, its interplanar spacing is 0.182nm. Fig. 9 This is the TEM image of the Cu-0.3In alloy current collector, whose interplanar spacing is 0.184nm.
[0073] Comparative Example 3
[0074] The negative electrode of the aqueous zinc-ion battery is a pure copper current collector. The cycle test diagram is as follows Fig.10 shown.
[0075] Example Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Alloy composition Cu-0.3Sn Cu-0.3Ag Cu-0.3In Cu Interplanar spacing 0.185nm 0.182nm 0.184nm 0.181nm Lattice mismatch with Zn 11.5% 12.9% 12.0% 13.4% Half-cell stable cycle number 2600 1500 1100 500
[0076] Table 1 - Comparison of alloy characteristics and properties of examples and comparative examples
[0077] After the cycle is completed, the battery is disassembled and the current collector is characterized by SEM. Fig.10As shown, vertical dendrite protrusions grow on the pure Cu current collector, which will pierce the diaphragm and cause battery short circuit during battery cycling; the Zn deposition on the Cu-0.3Ag current collector is messy, with uneven size and thickness, which may lead to unstable battery cycling; dead zinc falls off on the Cu-0.3Ag current collector, which will lead to a decrease in available Zn in subsequent cycles, thereby reducing battery performance; while the Zn on the Cu-0.3Sn current collector is deposited in a flat and dense manner without obvious protrusions, which can improve battery performance.
[0078] The present invention alloys copper with other metals to improve the lattice adaptation degree between zinc and current collector atoms, improve the reversibility of zinc deposition / deposition on the current collector, inhibit dendrite growth, and increase battery life. Therefore, the industrial application prospect of alloy current collector is relatively broad.
[0079] The present invention applies a copper alloy current collector to the negative electrode of an aqueous zinc ion battery, which can uniformly induce zinc deposition. The copper alloy current collector of the present invention can regulate the dissolution and deposition behavior of zinc ions in the battery. The copper alloy current collector and zinc foil are assembled into an asymmetric battery, which can maintain high reversibility of zinc deposition and release, uniformly induce zinc deposition and inhibit dendrite growth, thereby greatly improving the coulombic efficiency of the asymmetric battery.
Claims
1. A method for producing a copper alloy current collector for an aqueous zinc ion battery, characterized in that: The following steps are included: Step S1, weighing various metal powders according to weight percentage, including 0.1-3wt% of tin and the balance of copper; Step S2, moving each metal powder into a graphite crucible, placing the graphite crucible in a vacuum device, and maintaining the vacuum degree of the vacuum chamber at 20-1 Pa; Step S3, heating and smelting, the smelting temperature is controlled at 900-1500° C., and heating is stopped after all the metal powders are melted, and pouring is performed in a vacuum cavity and cooled to room temperature to obtain a copper alloy ingot; Step S4, cutting the copper alloy ingot into sheets with a thickness of 0.5 to 1 cm to obtain copper alloy sheets, Step S5, performing a first rolling treatment on the copper alloy sheet, and reducing the thickness of the copper alloy sheet to 200-400 μm by the first rolling treatment; and then performing a first annealing treatment on the copper alloy sheet. The first annealing treatment includes a heating stage, a heat preservation stage and a cooling stage, in which atmosphere protection is performed in the heating stage, the heat preservation stage and the cooling stage. In the heating stage, the heating rate is controlled at 5 to 10°C / min, in the heat preservation stage, the annealing temperature is controlled at 400 to 500°C, and the annealing heat preservation time is controlled at 1 to 4 hours. In the cooling stage, the copper alloy sheet is naturally cooled to room temperature in the atmosphere protection; Step S6, performing a second rolling treatment on the copper alloy sheet that has undergone the first annealing treatment, reducing the thickness of the copper alloy sheet to 70-150 μm by the second rolling treatment, and then performing a second annealing treatment on the copper alloy sheet. The second annealing treatment includes a heating stage, a heat preservation stage and a cooling stage. Atmosphere protection is performed in the heating stage, the heat preservation stage and the cooling stage. In the heating stage, the heating rate is controlled at 5-10°C / min. In the heat preservation stage, the annealing temperature is controlled at 400-500°C and the annealing holding time is controlled at 1-4 hours. In the cooling stage, the copper alloy sheet is naturally cooled to room temperature in the atmosphere protection. A copper alloy current collector for an aqueous zinc ion battery is prepared.
2. The method for producing a copper alloy current collector for an aqueous zinc ion battery according to claim 1, characterized in that: During the first annealing treatment, the heating rate is controlled at 8-10°C / min in the heating stage, the annealing temperature is controlled at 400-450°C and the annealing holding time is controlled at 1-2 hours in the holding stage; the thickness of the copper alloy sheet is thinned to 70-100 μm through the second rolling treatment, and during the second annealing treatment, the heating rate is controlled at 5-6°C / min in the heating stage, the annealing temperature is controlled at 460-500°C and the annealing holding time is controlled at 0.5-1 hour in the holding stage.
3. The method for producing a copper alloy current collector for an aqueous zinc ion battery according to claim 1, characterized in that: In the step S3, the smelting temperature is controlled at 900-1000°C, and the smelting time is controlled at 0.3-0.5 hours; in the step S5, during the first annealing process and the second annealing process, the atmosphere used for the atmosphere protection is a mixed atmosphere of hydrogen and argon.
4. A copper alloy current collector for an aqueous zinc ion battery, characterized in that: According to the production method of a copper alloy current collector for an aqueous zinc ion battery according to any one of claims 1 to 3, the copper alloy current collector comprises 0.1 to 3wt% of tin and the remainder of copper, as well as inevitable impurity elements, by weight percentage, wherein the tin element is completely dissolved in the copper matrix, and there is no enrichment of tin or copper elements at and within the grain boundaries, the grains are distributed in an equiaxed crystal shape, the grain radius is 2-5 microns, and the size difference of the grains in each direction is reduced to 0.1-0.5 microns.
5. The copper alloy current collector for an aqueous zinc ion battery according to claim 4, characterized in that: The copper alloy current collector also includes 0.1-3wt% indium or 0.1-3wt% silver by weight, wherein the indium element or the silver element is completely dissolved in the copper matrix, and there is no enrichment of tin element, copper element, indium element or silver element at and within the grain boundaries. The grains are distributed in an equiaxed crystal shape, the grain radius is 2-3 microns, and the size difference of the grains in each direction is reduced to 0.1-0.3 microns.
6. The copper alloy current collector for an aqueous zinc ion battery according to claim 4, characterized in that: The copper alloy current collector also includes 0.1-1wt% indium and 0.1-1wt% silver by weight, wherein tin, indium and silver are completely dissolved in the copper matrix, and there is no enrichment of tin, copper, indium or silver at and within the grain boundaries. The grains are distributed in an equiaxed crystal shape, the grain radius is 2-3 microns, and the size difference of the grains in each direction is reduced to 0.1-0.3 microns.
7. Application of the copper alloy current collector according to any one of claims 2 to 4 in an aqueous zinc ion battery, characterized in that: The negative electrode of the aqueous zinc ion battery comprises a whole obtained by pre-depositing a zinc sheet on the copper alloy current collector according to any one of claims 2 to 4.
Citation Information
Patent Citations
Copper alloy for negative current collector of lithium ion battery
CN104313386A
Cu-Sn-P copper alloy material with high tin content and preparation method thereof
CN113943875A
Zinc alloy negative electrode as well as preparation method and application thereof
CN113972351A
Copper alloy foil for negative electrode current collector of secondary battery, method for manufacturing copper alloy foil for negative electrode current collector of secondary battery, negative electrode for secondary battery, and secondary battery
JP5739044B1
Copper alloys capable of spinodal decomposition and a method of obtaining such alloys
US5196074A